2002
DOI: 10.1021/ie020154i
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination and Prediction of Gas Solubility Data for CO2 + H2O Mixtures Containing NaCl or KCl at Temperatures between 313 and 393 K and Pressures up to 10 MPa

Abstract: Gas solubility data of carbon dioxide (CO 2 ) in water (H 2 O) and aqueous sodium or potassium chloride (NaCl, KCl) solutions were measured by means of the static synthetic method in a temperature range from 313 to 393 K and pressures up to 10 MPa. The experimental data were compared to the results of other authors and to calculated values using an equation of state (EoS) approach. The calculations were enabled by the combination of the PSRK group contribution EoS with the LIFAC method for the prediction of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
152
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(169 citation statements)
references
References 19 publications
16
152
1
Order By: Relevance
“…Kiepe et al [33] calculated gas solubilities (isothermal P-x data) for the CO 2 -H 2 O system at the temperature and pressure of 313 393K and 0 10MPa by coupling the predictive Soave-Redlich-Kwong (PSRK) group contribution EOS with the model of LIFAC, and the prediction is in good agreement with the experimental data. Valtz et al [35] calculated vapour-liquid equilibrium (VLE) of the CO 2 -H 2 O system at the temperature and pressure of 278.2 318.2K and 0.464 7.963MPa by using a thermodynamic model.…”
Section: Thermodynamic Modeling 31 Review Of the Thermodynamic Modelmentioning
confidence: 87%
See 1 more Smart Citation
“…Kiepe et al [33] calculated gas solubilities (isothermal P-x data) for the CO 2 -H 2 O system at the temperature and pressure of 313 393K and 0 10MPa by coupling the predictive Soave-Redlich-Kwong (PSRK) group contribution EOS with the model of LIFAC, and the prediction is in good agreement with the experimental data. Valtz et al [35] calculated vapour-liquid equilibrium (VLE) of the CO 2 -H 2 O system at the temperature and pressure of 278.2 318.2K and 0.464 7.963MPa by using a thermodynamic model.…”
Section: Thermodynamic Modeling 31 Review Of the Thermodynamic Modelmentioning
confidence: 87%
“…(2) Kiepe et al [33] calculated VLE for the CO 2 -H 2 O-NaCl system at the temperature and pressure of 313.15 353.15K, 0 10MPa by using the combination of PSRK group contribution EOS with LIFAC model to account for the effect of strong electrolytes on the activity coefficients of nonelectrolytes. The prediction is in good agreement with the experimental data.…”
Section: Co 2 -H 2 O-nacl Systemmentioning
confidence: 99%
“…It has been reported that 0.9-3.6 mol% of CO 2 can be dissolved in brine, depending on pressure, temperature and brine composition (Rumpf et al 1994, Koschel et al 2006 Kiepe et al 2002). Before analyzing these relationships in more depth, it should be pointed out that CO 2 and brine are a reactive system, CO 2 reacts with water to form carbonic acid which subsequently dissociates (scheme 1) through a proton-relay mechanism that is catalyzed by several water molecules (Adamczyk et al 2009) Adamczyk et al (2009) studied these reactions at atmospheric pressure and found that the slowest step in scheme 1 is the forward reaction of (b), the hydration of CO 2 (aq) resulting in H 2 CO 3 .…”
Section: Thermodynamics Of Co 2 Dissolution Into Formation Brinementioning
confidence: 99%
“…Three experimentally measured points at CCS pressure conditions are also added to the graph. show experimental data points measured by Nighswander et al (1989), Li et al (2004) and Kiepe et al (2002) Moreover, the type of dissolved salt has an influence on CO 2 solubility. Yasunishi and Yoshda (1979) studied CO 2 solubilites at atmospheric pressure in a wide variety of salt solutions, these salts included NaCl, KCl, Na 2 SO 4 , MgCl 2 , CaCl 2 , K 2 SO 4 , MgSO 4 , BaCl 2 , AlCl 3 , Al 2 (SO 4 ) 3 among others.…”
mentioning
confidence: 98%
“…1 (b), the CO 2 solubility decreases with increasing salt concentration (molality, m, mol/kgH 2 O), salt-out effect, and the model captures not only the pressure effect on the CO 2 solubility but also the salting-out effect. [23,[25][26][27] …”
Section: Phase Equilibrium and Properties For Co 2 -H 2 O-nacl Systemmentioning
confidence: 99%